Race and Networks in the Job Search Process - Pedulla, David S.; Pager, Devah (American sociological review, 2019)
Racial disparities persist throughout the employment process, with African Americans experiencing significant barriers compared to whites. This article advances the understanding of racial labor market stratification by bringing new theoretical insights and original data to bear on the ways social networks shape racial disparities in employment opportunities. We develop and articulate two pathways through which networks may perpetuate racial inequality in the labor market: network access and network returns. In the first case, African American job seekers may receive fewer job leads through their social networks than white job seekers, limiting their access to employment opportunities. In the second case, black and white job seekers may utilize their social networks at similar rates, but their networks may differ in effectiveness. Our data, with detailed information about both job applications and job offers, provide the unique ability to adjudicate between these processes. We find evidence that black and white job seekers utilize their networks at similar rates, but network-based methods are less likely to lead to job offers for African Americans. We then theoretically develop and empirically test two mechanisms that may explain these differential returns: network placement and network mobilization. We conclude by discussing the implications of these findings for scholarship on racial stratification and social networks in the job search process.